Clarifying optimal outcome measures in intermittent and continuous laryngeal neuromonitoring. Issue 2 (1st December 2021) - Sinclair, Catherine F.; Buczek, Erin; Cottril, Elizabeth; Angelos, Peter; Barczynski, Marcin; Ho, Allen S.; Makarin, Viktor; Musholt, Thomas; Scharpf, Joseph; Schneider, Rick; Stack Jr, Brendan C.; Tellez, Maria J.; et al.
Abstract: Background: Intraoperative neuromonitoring (IONM) techniques have evolved over the past decade into intermittent IONM (I‐IONM) and continuous IONM (C‐IONM) modes of application. Despite many prior publications on both types of IONM, there remains uncertainty about what outcomes should be measured for each form of IONM. The primary objective of this paper is to define categories of benefit for I‐IONM/C‐IONM and to clarify and standardize their reporting outcomes. Methods: Expert review consensus statement utilizing modified Delphi methodology. Results: I‐IONM provides diagnosis, classification, and prevention of nerve injury through accurate and early nerve identification. C‐IONM provides real‐time information on nerve functional integrity and thus may prevent some types of nerve injury but cannot assist in nerve localization. Sudden mechanisms of nerve injury cannot be predicted or prevented by either technique. Conclusions: I‐IONM and C‐IONM are complementary techniques. Future studies evaluating the utility of IONM should focus on outcomes that are appropriate to the type of IONM being utilized.